Elasto-plastic behaviour and design of semi-compact circular hollow sections. (March 2020) - Meng, Xin; Gardner, Leroy; Sadowski, Adam J.; Rotter, J. Michael
Abstract: Previous research has revealed shortcomings in the current Eurocode 3 (EC3) provisions for the design of semi-compact (Class 3) cross-sections. These shortcomings arise primarily from the lack of utilisation of partial plastification in bending, leading to a step in the design resistance function at the boundary between Class 2 and 3 cross-sections and an underestimation of the available capacity. This affects the accuracy of resistance predictions in bending and under combined loading, and applies at both cross-sectional and member level. To address this issue, the use of an elasto-plastic section modulus, which lies between the plastic and elastic section moduli, has been proposed and employed in the design of semi-compact I- and box sections. The aim of the present study is to develop new cross-section and member buckling design rules incorporating the elasto-plastic section modulus for semi-compact circular hollow sections (CHS), and to assess their accuracy against existing experimental and freshly generated numerical data. Firstly, an experimental database, consisting of previous cross-section and member buckling test results on steel CHS, was established. A comprehensive numerical simulation programme was subsequently carried out; in this programme, finite element (FE) models were developed, validated and used for parametric studies, where over 600 numerical structural performance data on semi-compact CHS were generated. New sets of cross-section and member buckling design expressions featuring elasto-plastic section properties were then proposed and assessed against the test and numerical data. The proposals were shown to offer improved accuracy and design efficiency over the elastic EC3 methods. The reliability of the proposed elasto-plastic design rules was then confirmed through statistical analyses in accordance with EN 1990, demonstrating their suitability for inclusion into the next revision of EN 1993-1-1. Highlights: Existing cross-section and member buckling test data on CHS were collected. Numerical simulation was conducted to generate further data on CHS. New design rules were developed to capture the elasto-plastic behaviour of semi-compact CHS. Accuracy of the current Eurocode 3 and proposed methods were assessed and compared. Reliability of the proposed design rules was confirmed through statistical analyses.